2005
DOI: 10.1007/s00428-005-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

p63, cytokeratin 5, and P-cadherin: three molecular markers to distinguish basal phenotype in breast carcinomas

Abstract: Human breast carcinomas represent a heterogeneous group of tumors diverse in behavior, outcome, and response to therapy. However, the current system of pathological classification does not take into account biologic determinants of prognosis. The purpose of this study was to classify and characterize breast carcinomas based on variations in protein expression patterns derived from immunohistochemical analyses on tissue microarrays (TMAs). Therefore, 11 TMAs representing 168 invasive breast carcinomas were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
211
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(232 citation statements)
references
References 28 publications
18
211
0
3
Order By: Relevance
“…Our study confirms and extends the previously reported findings of the basal-like carcinoma immunophenotype. [5][6][7][8]10 In addition, we demonstrate the presence of in situ carcinoma as the likely precursor lesion for invasive basal-like carcinoma.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our study confirms and extends the previously reported findings of the basal-like carcinoma immunophenotype. [5][6][7][8]10 In addition, we demonstrate the presence of in situ carcinoma as the likely precursor lesion for invasive basal-like carcinoma.…”
Section: Discussionmentioning
confidence: 57%
“…5 The characteristic immunohistologic phenotype of these tumors is the 'triple negative' receptors of estrogen, progesterone and HER-2/neu, while expressing keratins CK5/6, CK14, CK17, vimentin and HER-1. [5][6][7][8][9][10][11] While the invasive basal-like neoplasms are reasonably well characterized morphologically and immunohistochemically, there is little data about the precursor lesion(s) for the entity.…”
mentioning
confidence: 99%
“…Out of these cases, 10 showed expression of basal/myoepithelial markers (ie, Ck5/6, Ck14, Ck17 and EGFR). 19,21,26,27,30,31 Although NGFR showed no prognostic significance in this cohort, when its expression was analysed in a cohort of 37 basal-like breast carcinomas, 26 NGFR showed a statistically significant association with lack of lymph node metastasis. In addition, initial analysis in 37 basal-like breast carcinomas has revealed statistically significant associations between NGFR expression and longer disease-free and overall survival.…”
Section: Discussionmentioning
confidence: 79%
“…For tissue microarray and whole tissue section immunohistochemical analysis, a cutoff of 10% unequivocally stained neoplastic cells was adopted for ER, PR, basal markers and EGFR, 30 whereas HER2 was scored according to the Herceptest scoring system. 38 For basal markers, only cytoplasmic staining was considered specific, for EGFR and HER2 only membranous staining was regarded as specific and for ER and PR, only nuclear staining was considered specific.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation